Analysing entrepreneurship education: a bibliometric survey pattern - Alexandros Kakouris; Panagiotis Georgiadis (Journal of Global Entrepreneurship Research, 2016)
Entrepreneurship education is an evolving field that confronts obstacles due to fragmentation issues and eclectic approaches that have to be resolved utilising robust educational theories and tools able to intrude effectively the entrepreneurial research discourse. Entrepreneurial learning is also the outcome of education and an unequivocal component of theorising about entrepreneurship. Based on explanatory bibliometric techniques, the present study examines, for the first time, how these terms have emerged in the extant entrepreneurship literature since eighties. A set of 7726 abstracts, retrieved from the SCOPUS database, is analysed through (key)word frequencies, co-occurrence networks and citations. Quantitative findings verify the customary picture for entrepreneurship education that exhibits low academic citation and loose connections with learning theories. The present data also reveal that the connection of entrepreneurship with lifelong learning settings, vocational training and career counselling is scarce in literature. Other "gaps" in research pertain to the comprehensive examination of experiential learning, advanced learning processes and education for innovation. The quantitatively identified shortage of the previous research topics is crucial for the future development of the field of entrepreneurship. Implications concern educational researchers in the field of entrepreneurship, educational agencies or policies as well as academic publishers.
Keywords: 650; Entrepreneurship; Entrepreneurship education; Entrepreneurial learning; Lifelong learning; Scientometrics; Bibliometrics